Intrathecal drug delivery for pain management: recent advances and future developments. (3rd August 2019) - Jain, Sameer; Malinowski, Mark; Chopra, Pooja; Varshney, Vishal; Deer, Timothy R.
ABSTRACT: Introduction : Chronic pain conditions of malignant and non-malignant etiology afflict a large group of the population and pose a vast economic burden on society. Intrathecal drug therapy is a viable treatment option in such patients who have failed conservative medical measures and less invasive pain management procedures. However, the clinical growth of intrathecal therapy in managing intractable chronic pain conditions continues to face many challenges and is likely underutilized secondary to its high-complexity and lack of understanding. Areas covered : This review will briefly discuss the history of intrathecal drug delivery systems (IDDS), cerebrospinal fluid (CSF) flow dynamics, types of IDDS, indications and patient profile suitable for this therapy, and risks and complications related to IDDS. We will also discuss challenges faced by physicians utilizing this therapy and the future changes that are needed for making this treatment modality more efficacious. Expert opinion : IDDS offer an effective therapy for pain control in patients suffering from chronic intractable pain conditions. These devices provide a safer alternative to oral opioid medications with reduced systemic side effects. Adherence to best practices and continued clinical and basic science research is important to ensure continuing success of this therapy.